2018
DOI: 10.1016/j.cell.2018.05.048
|View full text |Cite|
|
Sign up to set email alerts
|

CBFβ-SMMHC Inhibition Triggers Apoptosis by Disrupting MYC Chromatin Dynamics in Acute Myeloid Leukemia

Abstract: SUMMARY The fusion oncoprotein CBFβ-SMMHC, expressed in leukemia cases with chromosome 16 inversion, drives leukemia development and maintenance by altering the activity of the transcription factor RUNX1. Here we demonstrate that CBFβ-SMMHC maintains cell viability by neutralizing RUNX1-mediated repression of MYC expression. Upon pharmacologic inhibition of the CBFβ-SMMHC/RUNX1 interaction, RUNX1 shows increased binding at three MYC distal enhancers. There it represses MYC expression by mediating the replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 88 publications
(115 reference statements)
4
74
0
Order By: Relevance
“…Notably, emerging evidence has indicated that these ATF1 target genes, including MYC, BRAF, NRAS, BIRC2, and ID1, play important roles in cell apoptosis and proliferation in the progression of multiple cancers, including CRC. 39,43,44 Therefore, these findings suggest that ATF1 can facilitate CRC development, and most of that facilitation is due to the pathological activation of these oncogenic pathways.…”
Section: P Ro -G + E N H -G P Ro -G + E N H -T P Ro -T + E N H -G P Rmentioning
confidence: 88%
“…Notably, emerging evidence has indicated that these ATF1 target genes, including MYC, BRAF, NRAS, BIRC2, and ID1, play important roles in cell apoptosis and proliferation in the progression of multiple cancers, including CRC. 39,43,44 Therefore, these findings suggest that ATF1 can facilitate CRC development, and most of that facilitation is due to the pathological activation of these oncogenic pathways.…”
Section: P Ro -G + E N H -G P Ro -G + E N H -T P Ro -T + E N H -G P Rmentioning
confidence: 88%
“…MYC is highly expressed in human pluripotent stem cells (Knoepfler, 2008). As MYC expression is regulated by long-range enhancers in various cell types, we thought that MYC expression in the stem cells should be also dependent on long-range enhancers (Bahr et al, 2018;Cho et al, 2018;Dave et al, 2017;Herranz et al, 2014;Hnisz et al, 2013;Lovén et al, 2013;Pulikkan et al, 2018;Shi et al, 2013;Sur et al, 2012;Uslu et al, 2014;Zhang et al, 2016). Hence we used the iPSC line 253G1, which was generated via retroviral transduction of OCT4, KLF4 and SOX2 but without MYC, to test the functionality of STITCH (Nakagawa et al, 2007).…”
Section: Stitch Blocks the Interaction Of Myc With The Enhancer When mentioning
confidence: 99%
“…Further our transcriptome analysis revealed that down-regulation of MYC leads to decrease of genes involved in cholesterol synthesis and ribosomal assembly ( Figure 2). Genes related to ribosomes have been well known targets of MYC in various cell types, and are thought to contribute to increasing cell proliferation (Hofmann et al, 2015;Pulikkan et al, 2018;Uslu et al, 2014;van Riggelen et al, 2010;Zeller et al, 2006). Also MYC haploinsufficient mice showed reduction of cholesterol synthesis through down-regulation of genes involved in the process (Hofmann et al, 2015).…”
Section: The Myc Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the syncytins, a family of mammalian genes required for successful placentation, derive from genes encoding retrovirus envelope proteins, now conserved for other purposes [10]. Similarly, the neuronal protein Arc, which assembles into capsid-like structures that mediate communication between mammalian nerve cells, derives from the retroviral polyprotein Gag [11,12]. Exaptation of genes from non-retroviruses is also documented.…”
Section: Introductionmentioning
confidence: 99%